2022
DOI: 10.1108/intr-06-2021-0406
|View full text |Cite
|
Sign up to set email alerts
|

Go digital: can the money-gift function promote the use of e-wallet apps?

Abstract: PurposeOne of the impacts of the COVID-19 pandemic is that using an e-wallet – a contactless process – rather than a payment terminal is an intuitively safer option. This study is grounded in cognitive absorption theory and investigates how the use of the money-gift function influences the intention to continue using an e-wallet app.Design/methodology/approachUsing a cross-sectional approach, a structured questionnaire was designed and distributed to the target respondents in Malaysia through social media plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 99 publications
0
26
0
Order By: Relevance
“…This is also related to inadequate digital literacy of respondents. Supposedly, when Generation Z realizes the benefits of using e-wallet for their daily needs, a positive attitude will form towards it (Lim et al, 2021). In contrast to the results of research conducted by Yoon et al (2020) dan Yan et al (2021) which shows that the ease of use of e-wallet applications has a positive effect on user's intentions to use the application.…”
Section: Resultsmentioning
confidence: 83%
“…This is also related to inadequate digital literacy of respondents. Supposedly, when Generation Z realizes the benefits of using e-wallet for their daily needs, a positive attitude will form towards it (Lim et al, 2021). In contrast to the results of research conducted by Yoon et al (2020) dan Yan et al (2021) which shows that the ease of use of e-wallet applications has a positive effect on user's intentions to use the application.…”
Section: Resultsmentioning
confidence: 83%
“…The TPB prescribes that attitude, subjective norms, and PBC are the main variables that determine behavioral intention. The more positive one’s attitude, subjective norms, and PBC, the greater his/her behavioral intention (Ajzen, 1991 ; Lim et al, 2022 ). Attitude is the evaluation of an individual’s likes or dislikes towards performing a specific behavior; subjective norms refer to the social pressure perceived by an individual, reflecting the influence of others on his/her decision-making; and PBC is an individual’s perception of the difficulty of performing a specific behavior, which represents his/her awareness of the behavior that promotes or hinders its performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the TPB provides a reliable framework for studying the influencing factors of online takeout intention. Nonetheless, research needs to combine the antecedents of the TPB with other theories to comprehensively reveal the factors driving individual behavior (Ajzen, 1991 ; Lim et al, 2022 ). Taking the perceived risk of online takeout packaging as an antecedent of the TPB, this paper explains the purchase intention of online takeout from the perspective of environmental protection, thereby enriching and supplementing the study of TPB from the perspective of sustainable consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies have shown that perceived usefulness is a powerful predictor of customer behavior intention and acceptability (Aji et al, 2020;Ardiansah et al, 2020;Tun-Pin et al, 2019;Vincent & Sengupta, 2019). In the digital world, infrastructure supports the information distribution system, increasing the acceptability of technology (He et al, 2018), especially in e-wallet acceptance (Lim et al, 2022;Yang et al, 2021). Briefly, it is a user's cognitive expectation of how well the system will function.…”
Section: Factors Affecting E-wallet Acceptance Perceived Usefulness (Pu)mentioning
confidence: 99%
“…Further, ATT is expected to be a mediator between SC and acceptance. The study by (Lim et al, 2022) proved that SC has a positive impact on ATT because the more secure the users feel about the technology, the higher the satisfaction will be due to the positive attitude to accept the e-wallet. Persistent with this view, Yang et al (2021); Latupeirissa et al (2020) disclosed a positive effect of TR on ATT to use the e-wallet.…”
Section: Attitude (Att) -Mediatormentioning
confidence: 99%